Women’s contribution to local economic development: A study of women in cassava production and processing in Central Tongu District. - Mensah Obed, Sampson (2015)
A thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of MASTER OF SCIENCE IN